1998
DOI: 10.1097/00003643-199807000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Thiopentone and propofol: a compatible mixture?

Abstract: advantage of reducing the pain on injection, provides synergistic interaction, does not prolong recovery The physical compatibility of thiopentone and prowhen used for induction of anaesthesia, may reduce pofol mixtures was investigated. The investigations the incidence of convulsions and is cost-effective. used were macroscopic and microscopic observations, zeta potential and oil droplet size measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…At pH 7.0, the current was reduced to 86%; at pH 7.4, the current was reduced to 61%; and at pH 8.0, the current was reduced to 56%. *, p < 0.05. pental reduced the pain on injection of propofol more effectively than did lidocaine (Lee et al 1994;Paw et al 1998;Jones et al 1999). In these cases, the local concentration of the barbiturate may be high enough to suppress the purinergic responses at peripheral nerve endings in the vein wall.…”
Section: Discussionmentioning
confidence: 99%
“…At pH 7.0, the current was reduced to 86%; at pH 7.4, the current was reduced to 61%; and at pH 8.0, the current was reduced to 56%. *, p < 0.05. pental reduced the pain on injection of propofol more effectively than did lidocaine (Lee et al 1994;Paw et al 1998;Jones et al 1999). In these cases, the local concentration of the barbiturate may be high enough to suppress the purinergic responses at peripheral nerve endings in the vein wall.…”
Section: Discussionmentioning
confidence: 99%
“…According to a hypothesis, its reduction causes the propofol solution to migrate to the fat phase and reduces the amount of propofol in the aqueous phase, thereby reducing pain. [37] Soltani Mohammadi et al [28] conducted a study concluded that adding thiopental to propofol reduced pain caused by intravenous propofol injection.Studies on the physicochemical properties of the propofol-thiopental mixture have proven the compatibility of this combination, and found no trace of instability [41][42][43][44][45] . Anil Agarwal et al [11] conducted a study on pretreatment with thiopentone for prevention of pain associated with propofol injection.…”
Section: Introductionmentioning
confidence: 91%